Inhibitory effects of advanced glycation end‐products and Porphyromonas gingivalis lipopolysaccharide on the expression of osteoblastic markers of rat bone marrow cells in culture. (30th July 2015) - Sakamoto, E.; Mihara, C.; Ikuta, T.; Inagaki, Y.; Kido, J.; Nagata, T.
Abstract : Background and Objectives: Diabetes is a major risk factor for periodontitis and there is a close relationship between the degree of hyperglycemia and the severity of periodontitis. Advanced glycation end‐products (AGEs) accumulate in various tissues under diabetic conditions. AGEs in the periodontal tissues probably play a role in upregulating periodontal inflammation; however, the association of AGEs with the severity of periodontitis has not been fully clarified. Lipopolysaccharide from Porphyromonas gingivalis ( P ‐LPS) is a potent pathogenic factor in periodontitis. Although the independent effect of AGE or P ‐LPS on osteoblastic cells has been reported in vitro, the effect of adding both has not been clearly elucidated. In this study, to explore factors aggravating diabetic periodontitis, we investigated the effects of AGE and P ‐LPS on the expression of osteoblastic markers and the expression of inflammation‐related markers in vitro . Material and Methods: Rat bone marrow cells were cultured, and alkaline phosphatase activity and bone nodule formation were evaluated as osteoblastic markers. Reverse transcription–polymerase chain reaction was performed to determine the mRNA expression of molecules associated with bone and inflammation. Protein levels of osteocalcin and interleukin‐1β (IL‐1β) were measured using enzyme‐linked immunosorbent assay. Results: AGEs and P ‐LPS independently reduced alkaline phosphatase activity and bone nodule formation. The addition of both AGE and P ‐LPS (AGE+ P ‐LPS) further decreased these markers. Reverse transcription–polymerase chain reaction analysis revealed that AGE+ P ‐LPS markedly decreased the mRNA expression of osteoblast‐related molecules such as type 1 collagen, osteocalcin and Cbfa1, and markedly increased that of inflammation‐related molecules such as IL1β and S100A8. AGE and P ‐LPS decreased the protein level of osteocalcin and increased that of IL‐1β, and a further increase of IL‐1β was detected for AGE+ P ‐LPS. Conclusion: AGEs and P ‐LPS inhibited the expression of osteoblastic markers and increased the levels of inflammatory markers in rat bone marrow cells, suggesting that both AGE and P ‐LPS may be important factors associated with the aggravation of diabetic periodontitis.